A cross-layer framework for joint routing and rate adaptation in infrastructure Wireless Mesh Networks. (November 2016) - Narayan, D.G.; Mudenagudi, Uma
Highlights: New routing metric is analytically derived using IEEE 802.11 DCF mechanism. Routing metric and rate adaptation decisions are strongly related. Joint routing and rate adaptation framework is proposed by exploiting cross-layer information. Link quality is estimated using passive monitoring to minimize routing overhead. NS2 results reveals that joint framework performs better than existing approaches. Graphical abstract: Abstract: In this paper, we propose a cross-layer framework for joint routing and rate adaptation in multi-rate, Multi-Channel, Multi-Radio (MCMR) infrastructure Wireless Mesh Networks (WMNs). These networks use MCMR capabilities of mesh routers to achieve high performance. However, the MCMR nodes introduce interference in the multi-hop mesh networks and can degrade QoS. Thus, the design of routing metrics to improve the QoS has become an important research issue. Furthermore, as the routing metric and rate adaptation decisions are closely related, the joint approach is needed to improve the performance of the network. Towards this, we analytically derive our routing metric using IEEE 802.11 Distributed Coordination Function (DCF) basic access mechanism. Using this model, we propose Passive Interference and Delay Aware (P-IDA) routing metric which estimates the delay and interference by exploiting cross-layer information. We extend the work by performing joint routing and rate adaptation. The simulation results using NS2 reveal that proposed framework improves throughput and delay compared to existing approaches with reduced routing overhead.